Illuminated Darkness: Exiles and Émigrés in the Golden Age of Hollywood. Issue 1 (3rd May 2016) - Berger, Doris
Abstract: Looking at film history through the lens of social and political histories, this article presents the contributions of German-speaking exiles and émigrés that helped shape Hollywood's Golden Age. The text follows the narrative of the exhibition Light & Noir: Exiles and Émigrés in Hollywood, 1933 – 1950 that I developed for the Skirball Cultural Center in Los Angeles. It expands upon specific émigrés, their paths to the US, their contributions to Hollywood, and their sense of solidarity with one another.